Falkland Islands Peatland carbon data - Payne, Richard J (PANGAEA, 2019)
These data describe peat initiation and development in the Falkland Islands, South Atlantic. The datasets presented represent a combination of primary data collection and our compilation of previously-published data. The 'falklands_basal_dates' file lists radiocarbon dates which can be considered to represent peat initiation. Data are for: site name, location (northing/easting), radiocarbon date details (labID/age/error), basal depth, data source (reference given where data is secondary) and a brief description of the basal stratigraphy. The 'falklands_core_properties' dataset gives details of peat properties for cores from ten sites across East Falkland sampled in this study. Data are for: site codes (locations as listed in 'falklands.basal.dates), bulk density (determined by water displacement and drying at 105C), loss on ignition (combustion at 550C), %carbon (elemental analysis) and modelled age using Bacon. The 'falklands_depths' dataset gives measured peat depth for 371 sites. Depths listed are means of variable numbers of individual site measurements with a maximum measurable depth of 250cm. Full details of all datasets are given in the accompanying paper. Collectively the data presented here give the first synthesis of peat age and properties in the Falkland Islands.
Keywords: Basal; bog; Carbon; Initiation; Mire; peat; Peatland